How Generations Remember Conflicting Histories and Shared Memories in Post-War Bosnia and Herzegovina - Palmberger, Monika (Springer Nature, 2016)
This book provides a profound insight into post-war Mostar, and the memories of three generations of this Bosnian-Herzegovinian city. Drawing on several years of ethnographic fieldwork, it offers a vivid account of how personal and collective memories are utterly intertwined, and how memories across the generations are reimagined and 'rewritten' following great socio-political change. Focusing on both Bosniak-dominated East Mostar and Croat-dominated West Mostar, it demonstrates that, even in this ethno-nationally divided city with its two divergent national historiographies, generation-specific experiences are crucial in how people ascribe meaning to past events.